There’re CRISPRs in My Yogurt: A Discovery-Based CURE at the Intersection of Industrial Food Production and the Human Microbiome - Petrie, Katherine L. (Frontiers in Microbiology, 2020)
Support for undergraduate laboratory education based on a CURE (Course-based Undergraduate Research Experience) model is more widespread than ever. By giving students the opportunity to conduct genuine research in laboratory courses they are required to take, CUREs can expose more students to scientific practice and have the potential to make science more inclusive, especially when research topics have direct impact on students’ lives. Here, I present a new microbiology CURE module where students explore the real-world intersection between industrial food production and the human microbiome. In this module, students sequence CRISPR arrays in the genomes of lactic acid bacteria they isolate from yogurt. Natural CRISPRs (Clustered Regularly Interspaced Short Palindromic Repeats) act as the bacterial immune system. When a bacterial cell survives viral infection, it can incorporate a bit of that virus’s DNA into its own genome, and produce small RNA guides that surveil the cell, ready to deploy virus-destroying enzymes if matching DNA from a fresh viral infection is detected. This viral immunity is of particular interest in the fermentation industry, since viral infection can destroy stocks of starter cultures and batches of product. Commercial producers of lactic acid bacteria for yogurt production often endeavor to produce strains with large CRISPR arrays and robust immunities. With this context, students are given the task of cataloging the viral immunities found in both commercial and traditionally produced yogurt, and exploring their potential impact on human health. Wet-lab practices (strain isolation, PCR, Sanger sequencing) are combined with bioinformatic and literature sleuthing to identify the viruses to which bacteria are immune and explore whether consumption of these strains could impact human health via interactions with the human microbiome. Here, a detailed implementation of the module is presented with guides for educators and students.